XANTHONES FROM THE TWIGS OF THE VIETNAMESE CALOPHYLLUM CERIFERUM GAGNEP. EX STEVENS - Thi Minh Hang, Nguyen; Van Hung, Nguyen; Quyet Chien, Nguyen (Vietnam Journal of Science and Technology, 2017)
Three xanthones have been isolated from the dichloromethane extract of the twigs of the Vietnamese Calophyllum ceriferum Gagnep. Ex Stevens collected at Ninh Thuan province. Their structures were elucidated as 1,7-dihydroxy-2,3,8-trimethoxyxanthone, 1,7-dihydroxyxanthone and 1,6-dihydroxy-5,7-dimethoxyxanthone by spectroscopic analyses.